(untitled) (European Journal of Formal Sciences and Engineering, 2020)
Industrial attentiveness and demand for natural bioactive compounds are rising continuously, regarding their growing commercial values in nutrition, pharmaceuticals, cosmetics and many other industries. The progress in ultrasound technology has spread the use of ultrasonication on a broad field of application areas, including extraction of bio-materials from plant sources. Ultrasound-assisted extraction is a powerful alternative to conventional techniques, in terms of extracting bio-compounds from variable kinds of matrices, higher efficiency, reduced extraction time, toxic-free operation, lower energy demand, lesser water consumption and better extract quality. Existing research pointed out that the reactor configuration is vital for maximizing the efficacy of extraction process, however basic reactor configurations that were mainly used in the literature may not be feasibly adapted to full-scale industrial applications. In this study, an investigation on possible improvements and modifications to existing reactor designs are discussed, such as detecting the optimum frequency range of ultrasound transmission depending on the material rheology and composition, possible modifications in beam-forming by means of frequency modulation and finally transmitting the waves in combination of different frequencies.